2007
DOI: 10.1095/biolreprod.106.057778
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Chromosomal Risk Following Intracytoplasmic Sperm Injection in the Mouse

Abstract: To investigate whether cytogenetic risks occur using the mouse intracytoplasmic sperm injection (ICSI) technique, the incidence of chromosome aberrations was compared in one-cell embryos produced by ICSI technique and those by conventional in vitro fertilization (IVF) technique. Spermatozoa were incubated in TYH medium for 1.5-2 h before IVF insemination. For the ICSI technique, spermatozoa were incubated in five different media: TYH, Hepes-buffered TYH (H-TYH), modified CZB (mCZB), Hepes-buffered mCZB (H-mCZB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 47 publications
2
45
3
Order By: Relevance
“…The previous studies found that when mouse uncapacitated spermatozoa with intact acrosome were used for ICSI following short incubation (≤0.5 h) in TYH, incidence of structural chromosome aberrations in resultant zygotes was approximately 7%. When spermatozoa underwent capacitation and acrosome reaction following incubation in TYH for 2-2.5 h, the incidence was reduced to 3.8% [10,23]. In the present study, however, the incidence (23.4%) was unaccountably high when spermatozoa were treated with ionophore under the no-incubation.…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…The previous studies found that when mouse uncapacitated spermatozoa with intact acrosome were used for ICSI following short incubation (≤0.5 h) in TYH, incidence of structural chromosome aberrations in resultant zygotes was approximately 7%. When spermatozoa underwent capacitation and acrosome reaction following incubation in TYH for 2-2.5 h, the incidence was reduced to 3.8% [10,23]. In the present study, however, the incidence (23.4%) was unaccountably high when spermatozoa were treated with ionophore under the no-incubation.…”
Section: Discussioncontrasting
confidence: 73%
“…Bicarbonate-buffered TYH [16] and hepes-buffered H-TYH [10] were used as media for preparing spermatozoa. When spermatozoa were treated with ionophore, the concentration of calcium in TYH was doubled to effectively induce the acrosome reaction [17].…”
Section: Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the spermatazoan chromosomes in a variety species can be easily visualized using these oocytes in combination with ICSI techniques [25][26][27][28]. Therefore, the present study carried out an assessment of Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of oocytes by sperm, subsequent formation of male pronucleus (MPN) and their chromosomal integrity can be considered as indicators for fertilizing ability of spermatozoa. Furthermore, these indicators can be monitored by microinjection into mouse oocytes in mouse [24,25], whale [26] and human [27,28] spermatozoa.…”
Section: Introductionmentioning
confidence: 99%